Household inflation expectations and consumer spending: Evidence from panel data - Mary A. Burke; Ali Ozdagli (Federal Reserve Bank of Boston, 2013)
With nominal interest rates at the zero lower bound, an important question for monetary policy is whether, as predicted in prior theoretical work, an increase in inflation expectations would boost current consumer spending. Using survey panel data for the period from April 2009 to November 2012, we examine the relationship between a household's inflation expectations and its current spending by taking into account other factors, such as the household's wage growth expectations, the uncertainty surrounding its inflation expectations, macroeconomic conditions, and unobserved heterogeneity at the household level We examine spending behavior for large consumer durables as well as for nondurable goods. No evidence is found that consumers increase their spending on large home appliances and electronics in response to an increase in their inflation expectations. In most models, the estimated effects are small, negative, and statistically insignificant. However, consumers do appear more likely to purchase a car as their short-run inflation expectations rise. Additionally, in some models, spending on nondurable goods increases with short-run expected inflation. These estimated effects on nondurables spending are modest, not highly robust, and appear to be driven by the behavior of homeowners who did not have a mortgage. These findings are surprising because theory predicts that consumption of durable goods should be more sensitive to real interest rates than consumption of nondurable goods. During a large portion of our sample period, prices for large appliances were falling, either in absolute terms or in relation to the overall consumer price index, a fact that may help to explain our results. In addition, consumers in our sample, on average, did not expect their nominal income growth to match inflation, and therefore an increase in expected inflation would create a negative income effect that discourages spending in both the present and the future. The findings suggest that, as a policy measure, raising inflation expectations may not be effective in boosting present consumption.
Keywords: D12; D84; D91; E52; 330